Evaluation Growth of Hydroponic Fodder With Different Lighting Treatment to Increase Forage Productivity - Respati, Adib Norma; Wulandari, Suci; Kusuma, Satria Budi; Firmansyah, Wahyu; Ramadhan, Firli; Bahariawan, Amal (International Journal of Technology, Food and Agriculture, 2025)
This study was aimed to determine the effect of lighting and plant type on growth of hydroponic fodder to increase forage productivity. This study used a randomized complete factorial design. The first factor was plant type consisted of maize (Zea mays), mung bean (Vigna radiata L) and rice (Oryza sativa). The second factor was lighting treatment consisted of 12 hours and 24 hours. Each treatment was replicated 6 times. The variables measured were plant growth parameters consisted of plant height, leaves number, width of leave and length of leave. Data was analyzed using Analysis of Variety (ANOVA) and the difference between means was analyzed using Duncan’s Multiple Range Test (DMRT). The result showed that plant type increase in height, number of leaves, width and length of leave along with the ages plant. Maize showed the highest of plant height and numbers of leaves. Lighting 12 hours showed the best lighting to support plant height, then lighting 24 hours support to width of leaves. The conclusion of the study showed that the best growth results were corn plants with 12-hour lighting treatment.